Health Service Procedures for BPJS Participants in the Inpatient Room of Lasinrang General Hospital - Rais, Muh Kardi; Ridwan, Ridwan; Harum, Habil; Rudini, Muh; Pratiwi, Siska Wijayanti (PSPP JOURNALS, 2024)
Hospital services (RS), are an important public service and are needed in an effort to fulfill health demands. Services for the poor are one aspect implemented by health service providers such as Hospitals through after-sales services by utilizing BPJS funds as operational service activities. The type of research used is a survey system with a descriptive design. The population of the study was all BPJS participant patients who utilized inpatient services during the study, totaling 101 people who were also research samples based on the exhaustive sampling method where the entire population was sampled. The results of the study showed that BPJS participants who utilized health services at Lasinrang General Hospital, Pinrang Regency were mostly in the 20-29 year age group (32.7%), more were women (63.4%) with junior high school education (46.5%) and more worked as farmers (24.8%), more BPJS participant patient admission procedures stated that they were in the good category (69.3%), more doctor services stated that they were in the good category (67.3%), more nurse services stated that they were in the good category (65.3%) and more drug services for BPJS participant patients stated that they were in the good category (72.3%). The suggestion put forward in this study is the need to conduct training on excellent service in order to improve skills in providing services, especially to BPJS participants and treatment planning using the drug procurement method through distributors so that if the drug runs out, the distributor can be contacted and this will support the efficiency and effectiveness of drug procurement that meets the needs of patients, especially BPJS participants who utilize health services at the hospital.